Anterior Cruciate Ligament–Deficient Patients With Passive Knee Joint Laxity Have a Decreased Range of Anterior-Posterior Motion During Active Movements. (May 2013) - Boeth, Heide; Duda, Georg N.; Heller, Markus O.; Ehrig, Rainald M.; Doyscher, Ralf; Jung, Tobias; Moewis, Philippe; Scheffler, Sven; Taylor, William R.
Background: Although instability of the knee joint is known to modify gait patterns, the amount that patients compensate for joint laxity during active movements remains unknown. Purpose: By developing a novel technique to allow the assessment of tibiofemoral kinematics, this study aimed to elucidate the role of passive joint laxity on active tibiofemoral kinematics during walking. Study Design: Controlled laboratory study. Methods: Using motion capture, together with combinations of advanced techniques for assessing skeletal kinematics (including the symmetrical axis of rotation approach [SARA], symmetrical center of rotation estimation [SCoRE], and optimal common shape technique [OCST]), a novel noninvasive approach to evaluate dynamic tibiofemoral motion was demonstrated as both reproducible and repeatable. Passive and active anterior-posterior translations of the tibiofemoral joint were then examined in 13 patients with anterior cruciate ligament (ACL) ruptures that were confirmed by magnetic resonance imaging and compared with those in their healthy contralateral limbs. Results: Passive tibial anterior translation was significantly greater in the ACL-ruptured knees than in the contralateral healthy controls. However, the femora of the ACL-ruptured knees generally remained more posterior ( 3 mm) relative to the tibia within a gait cycle of walking compared with the healthy limbs. Surprisingly, the mean range of tibiofemoral anterior-posterior translation over an entire gait cycle was significantly lower in ACL-ruptured knees than in the healthy joints ( P = .026). A positive correlation was detected between passive laxity and active joint mobility, but with a consistent reduction in the range of tibiofemoral anterior-posterior translation of approximately 3 mm in the ACL-deficient knees. Conclusion: It seems that either active stabilization of tibiofemoral kinematics or anterior subluxation of the tibia reduces joint translation in lax knees. This implies that either a muscular overcompensation mechanism or a physical limitation due to secondary passive stabilizers occurs within the joint and thus produces a situation that has a reduced range of active motion compared with knees with physiological stability. Clinical Relevance: The reduced range of active tibiofemoral translation suggests overloading of the passive structures in passively lax knees, either through excessive muscular action or joint subluxation, and could provide a plausible mechanism for explaining posttraumatic degeneration of cartilage in the joint.